The Enduring Popularity of the Cabinet of Curiosities: Why French Guiana's Museums will not be Decolonized - Fuggle, Sophie (Museum and Society, 2025)
This article considers the persistence of 'cabinet of curiosities' style museums in French Guiana, France’s largest overseas département [department], within the wider context of decolonizing agendas found in mainland France and the Global North more generally. The central claim is that it is impossible to truly engage in decolonial praxis in places where colonial forms of governance still exist. It also suggests that to understand how and why the museum cannot fully be decolonized requires moving focus from institutions found in metropolitan centres to those located at the peripheries. Two museums will provide the focus of the analysis here – the Musée Alexandre Franconie in Cayenne and the Musée du Planeur Bleu in Cacao. The article will explore the ongoing local popularity of these museums where other larger scale 'postcolonial' museum projects have failed or stalled. The article will conclude by suggesting that while there do exist examples of museography in French Guiana that offer alternatives to both types of project, these are limited in scope and public engagement.